PENGGUNAAN SHUUJOSHI YO DAN NE DALAM ANIME KOE NO KATACHI KARYA NAOKO YAMADA - Singgih, Muhammad Arya; Aibonotika, Arza; Widiati, Sri Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Film is a form of communication media that can have an influencereaching all social segments of society. In the film there are also many speech acts from linguistic elements which function as an introduction for us in understanding the content that the film will convey. Sociolinguistic studies that can be studied in films are the use of words or particles in conversational sentences between characters, for example the use of final particles (Shuujoshi) which are widely used in Japanese with the aim of emphasizing the speaker's intentions. In this research, the data source chosen was the animated film Koe No Katachi by Naoko Yamada. This animated film uses a lot of Shuujoshi which are used in various situations. This research only analyzes Shuujoshi, namely Shuujoshi Yo and Ne. This research method uses the Descriptive Method, namely by describing the Sguujoshi Yo and Ne data contained in the animated film Koe No Katachi.Key words: Film, Function, Shuujoshi